2014
DOI: 10.1016/j.jvs.2014.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral arterial disease, gender, and depression in the Heart and Soul Study

Abstract: Background Despite the high prevalence of peripheral artery disease (PAD) in women, risk factors for PAD in women are not well understood. Methods Gender-specific risk factors for PAD were examined in a prospective cohort study of 1024 patients (184 women and 840 men) with stable coronary artery disease who were recruited between 2000 to 2002. Logistic regression models were used to evaluate associations between traditional and non-traditional risk factors and PAD in both men and women. Results 11% of wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 41 publications
1
27
0
4
Order By: Relevance
“…Ankle-brachial-index to screen for PAD is an inexpensive test for risk stratification in women and men, but unfortunately is not reimbursed for use for cardiac risk stratification by most payers. In women and men with stable IHD and PAD, depression was independently associated with PAD in women, and smoking and elevated fibrinogen levels with PAD in men 33 . Women with PAD who undergo vascular intervention are more likely to be older, have more severe and complex disease, and are at risk of adverse outcomes with higher rates of transfusion and embolism, although they have similar procedural success as men 34 .…”
Section: Risk Factorsmentioning
confidence: 89%
“…Ankle-brachial-index to screen for PAD is an inexpensive test for risk stratification in women and men, but unfortunately is not reimbursed for use for cardiac risk stratification by most payers. In women and men with stable IHD and PAD, depression was independently associated with PAD in women, and smoking and elevated fibrinogen levels with PAD in men 33 . Women with PAD who undergo vascular intervention are more likely to be older, have more severe and complex disease, and are at risk of adverse outcomes with higher rates of transfusion and embolism, although they have similar procedural success as men 34 .…”
Section: Risk Factorsmentioning
confidence: 89%
“…This novel finding of poorer mental health in women with IC at baseline parallels recent data suggesting depression as one of the strongest risk factors for PAD in women. 29 Poorer mental health parameters contribute to greater physical inactivity, which in turn induces insulin resistance and microvascular dysfunction, 30 rendering women more susceptible to development of PAD.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cross-sectional design of the present study does not allow firm conclusions to be drawn regarding the nature of the relationship between PAD and depression. Even though a previous study found no difference in depressive symptomatology before and after the effective treatment of PAD (12) -suggesting that depression is not a consequence of PAD-related functional limitations -; at this point, it is not clear whether depressive symptoms contribute to the pathogenesis of PAD or whether the limitations caused by this cardiovascular disorder exacerbates depressive symptoms or even so, whether the relationship between the two conditions is rather bidirectional as suggested by a prospective cohort study (13). It is also possible that the relationship between the two disorders can be traced back to the influence of one or more external variables -such as the increased production of inflammatory cytokines (14) -that seems to be a correlate of both conditions.…”
Section: Discussionmentioning
confidence: 82%